Experimental and Theoretical Studies on the Magnetic Anisotropy in Lanthanide(III)‐Centered Fe3Ln Propellers1. Issue 34 (15th July 2015) - Rigamonti, Luca; Nava, Andrea; Boulon, Marie‐Emmanuelle; Luzon, Javier; Sessoli, Roberta; Cornia, Andrea
Abstract Compounds [Fe3Ln(tea)2(dpm)6] (Fe3Ln; Ln= Tb–Yb, H3tea=triethanolamine, Hdpm=dipivaloylmethane) were synthesized as lanthanide(III)‐centered variants of tetrairon(III) single‐molecule magnets (Fe4) and isolated in crystalline form. Compounds with Ln=Tb–Tm are isomorphous and show crystallographic threefold symmetry. The coordination environment of the rare earth, given by two tea3− ligands, can be described as a bicapped distorted trigonal prism with D3 symmetry. Magnetic measurements showed the presence of weak ferromagnetic Fe⋅⋅⋅Ln interactions for derivatives with Tb, Dy, Ho, and Er, and of weak antiferromagnetic or negligible coupling in complexes with Tm and Yb. Alternating current susceptibility measurements showed simple paramagnetic behavior down to 1.8 K and for frequencies reaching 10000 Hz, despite the easy‐axis magnetic anisotropy found in Fe3Dy, Fe3Er, and Fe3Tm by single‐crystal angle‐resolved magnetometry. Relativistic quantum chemistry calculations were performed on Fe3Ln (Ln=Tb–Tm): the ground J multiplet of Ln3+ ion is split by the crystal field to give a ground singlet state for Tb and Tm, and a doublet for Dy, Ho, and Er with a large admixture of mJ states. Gyromagnetic factors result in no predominance of gz component along the threefold axis, with comparable gx and gy values in all compounds. It follows that the environment provided by the tea3− ligands, though uniaxial, is unsuitable to promote slow magnetic relaxation in Fe3Ln species.